Atypical dermatophytosis of glabrous skin caused by Paecilomyces lilacinus – case report - Kalbarczyk, Leszek; Ławrynowicz, Jan (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Tinea cutis glabrae is a classical dermatophytic infection; however, rare cases of this disease are caused by fungi which inhabit the soil. Clinical changes in such cases are usually different and the diagnosis may be difficult. Objective. Presentation of a case of atypical tinea cutis glabrae caused by Paecilomyces lilacinus – a mould living in soil and rotten wood. Case report. A 59-year-old woman was referred to us with erythematous and desquamative plaque of 6 months duration located on the forearm. Previous mycological examination (in a different dermatological centre) was negative and the patient was unsuccessfully treated with antibiotics for bacterial infection. The diagnosis of paecilomycosis was made after repeated mycological examinations with the microculture method. Conclusions. We recommend fungal microculture as a method for verification in the diagnosis of atypical cases of tinea cutis glabrae.